Answer:
1) C
2) B
3) D
4) B
5) A
6) C
7) B
8) D
9) A
10) B
Explanation:
Equation of a straight line is y= m x + c
m = slope
c is y- intercept
1) y = (-1/2)x + c
substitute (5,-2) for (x, y) points in the equation above
c = (1/2)
Therefore, the equation of the line is y = (-1/2)x + (1/2)
substituting the options A to D in to the equation to check for equality we find that option C does not lie on the Line it should have been (4, -1.5)
2) y = (3/4)x + c
substitute (3,3) for (x, y) points in the equation above
c = (3/4)
Therefore, the equation of the line is y = (3/4)x + (3/4)
substituting the options A to D in to the equation to check for equality we find that option B does not lie on the Line it should have been (-6, -3.75)
3) y = (-1/5)x + c
substitute (-7,2) for (x, y) points in the equation above
c = (3/5)
Therefore, the equation of the line is y = (-1/5)x + (3/5)
substituting the options A to D in to the equation to check for equality we find that option D does not lie on the Line it should have been (4, -0.2)
4) y = (1/2)x + c
substitute (9,3) for (x, y) points in the equation above
c = (-3/2)
Therefore, the equation of the line is y = (1/2)x - (3/2)
substituting the options A to D in to the equation to check for equality we find that option B does not lie on the Line it should have been (6, 1.5)
5) y = (-2/3)x + c
substitute (5,3) for (x, y) points in the equation above
c = (1/3)
Therefore, the equation of the line is y = (-2/3)x + (1/3)
substituting the options A to D in to the equation to check for equality we find that option A does not lie on the Line it should have been (-3, 2.333)
6) y = (1/4)x + c
substitute (5,2) for (x, y) points in the equation above
c = (3/4)
Therefore, the equation of the line is y = (1/4)x + (3/4)
substituting the options A to D in to the equation to check for equality we find that option C does not lie on the Line it should have been (4, 1.75)
7) y = (-3/2)x + c
substitute (3,-4) for (x, y) points in the equation above
c = (1/2)
Therefore, the equation of the line is y = (-3/2)x + (1/2)
substituting the options A to D in to the equation to check for equality we find that option B does not lie on the Line it should have been (2, -2.5)
8) y = (3/5)x + c
substitute (3,2) for (x, y) points in the equation above
c = (1/5)
Therefore, the equation of the line is y = (3/5)x + (1/5)
substituting the options A to D in to the equation to check for equality we find that option D does not lie on the Line it should have been (-4, -2.2)
9) y = (1/3)x + c
substitute (5,1) for (x, y) points in the equation above
c = (-2/3)
Therefore, the equation of the line is y = (1/3)x - (2/3)
substituting the options A to D in to the equation to check for equality we find that option A does not lie on the Line it should have been (6, 1.333)
10) y = (-3/4)x + c
substitute (-5,4) for (x, y) points in the equation above
c = (1/4)
Therefore, the equation of the line is y = (-3/4)x + (1/4)
substituting the options A to D in to the equation to check for equality we find that option B does not lie on the Line it should have been (-2, 1.75)